Genomic Analysis Highlights the Role of the JAK-STAT Signaling in the Anti-Proliferative Effects of Dietary Flavonoid—'Ashwagandha' in Prostate Cancer Cells. Issue 2 (2010) - Aalinkeel, Ravikumar; Hu, Zihua; Nair, Bindukumar B.; Sykes, Donald E.; Reynolds, Jessica L.; Mahajan, Supriya D.; Schwartz, Stanley A.
Abstract : Phytochemicals are dietary phytoestrogens that may play a role in prostate cancer prevention. Forty percent of Americans use complementary and alternative medicines (CAM) for disease prevention and therapy. Ashwagandha ( Withania somnifera ) contains flavonoids and active ingredients like alkaloids and steroidal lactones which are called 'Withanolides'. We hypothesize that the immunomodulatory and anti-inflammatory properties of Ashwagandha might contribute to its overall effectiveness as an anti-carcinogenic agent. The goal of our study was gain insight into the general biological and molecular functions and immunomodulatory processes that are altered as a result of Ashwagandha treatment in prostate cancer cells, and to identify the key signaling mechanisms that are involved in the regulation of these physiological effects using genomic microarray analysis in conjunction with quantitative real-time PCR and western blot analysis. Ashwagandha treatment significantly downregulated the gene and protein expression of proinflammatory cytokines IL-6, IL-1β, chemokine IL-8, Hsp70 and STAT-2, while a reciprocal upregulation was observed in gene and protein expression of p38 MAPK, PI3K, caspase 6, Cyclin D and c-myc. Furthermore, Ashwagandha treatment significantly modulated the JAK-STAT pathway which regulates both the apoptosis process as well as the MAP kinase signaling. These studies outline several functionally important classes of genes, which are associated with immune response, signal transduction, cell signaling, transcriptional regulation, apoptosis and cell cycle regulation and provide insight into the molecular signaling mechanisms that are modulated by Ashwagandha, thereby highlighting the use of this bioflavanoid as effective chemopreventive agent relevant to prostate cancer progression.